HUBUNGAN KUALITAS RUANG TERBUKA HIJAU TERHADAP TINGKAT STRES MASYARAKAT PERKOTAAN DI KOTA DENPASAR - Permana Putra, Ida Bagus Eka; Adhika, I Made; Pujaastawa, I. B. G. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 17 No 2 (2023)DO - 10.24843/EJES.2023.v17.i02.p07, 2023)
Urbanization has an impact on increasing the number of residents in urban areas. This increase has led to increasing problems faced by urban communities such as increased traffic jams, air pollution, employment problems and other problems that tend to cause urban society's aggressiveness and stress to increase. One way to reduce stress is to do activities in open green spaces (RTH). This research was conducted to analyze the quality of open green space in Denpasar City, calculate the stress level of the people in Denpasar City, analyze the relationship between the quality of open green space and the stress level of the people of Denpasar City. This research was conducted by collecting information about the quality of open green space through observation and questionnaires at Sewaka Dharma City Park, Puputan Badung Field (I Gusti Ngurah Made Agung), and Niti Mandala Renon Field. The total number of respondents taken was 210 respondents. The stress value is measured using the perceived stress scale score (PSS-10). The results showed that the community had a moderate stress level with an average PSS score of 20.96. As many as 86% of respondents stated that the open green space in Denpasar was clean, 80% of respondents stated that the air quality in open green space was cool, 56% of respondents stated that the placement of vegetation was comfortable, 41% of respondents stated that the smell of waste in open green space was not disturbing, and 60% of respondents stated that the conditions of the facilities in open green space were good. The quality of open green space has a real relationship to the stress level of the people of Denpasar City (p value = 0.037). This research is expected to provide information to the government and the public regarding the use and maintenance of city parks. Keywords: urban; green space; stress; park